If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + (-8) = 3x + 2 5x + -8 = 3x + 2 Reorder the terms: -8 + 5x = 3x + 2 Reorder the terms: -8 + 5x = 2 + 3x Solving -8 + 5x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + 5x + -3x = 2 + 3x + -3x Combine like terms: 5x + -3x = 2x -8 + 2x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + 2x = 2 + 0 -8 + 2x = 2 Add '8' to each side of the equation. -8 + 8 + 2x = 2 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 2 + 8 2x = 2 + 8 Combine like terms: 2 + 8 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| f(n)=n^2-n-30 | | -(-1-2x)-x--2/3=5 | | 4x+3=2x+(-11) | | -r+7=6 | | 2/3x+(-2)=10 | | 5x-2=45 | | -32=8 | | 88-41x=26-41x | | F(x)=x^2+8x+12 | | 9(x-9)+6=9x+6 | | x+(-9)=3 | | -7=21r | | y/6=2/3.9 | | 2(n+6)+4n=18 | | 10x^2+3x-9=0 | | (7y-9)2=(6y+3)3 | | F(t)=t^2+7t-60 | | 9+7x+7x=121 | | 3(6x-7)(5x+2)=0 | | 5x+2[3x+(-4)]=14x+7 | | x+5x+2-6-3x-4=2x-10+x-6 | | -9t^2=400 | | -(-1-2x)-x-2/3=5 | | 10+6x=45-8x | | 6(x-5)+2=6x+7 | | (-x+3)+(4x-10)= | | 7x+4x+10=120 | | F(x)=-4x^2+4x-24 | | 13+13w=8+5w | | 8x+3+(-2x)+5=3-4x | | 5/21-2/15 | | 5.4+(-3)=8.4x+9 |